Xác định hàm lượng chì trong bụi sa lắng trên đường Nguyễn Trãi, Hà Nội - Huy, Đỗ Quang; Huyền, Huỳnh Thu; Toàn, Ngụy Ngọc; Vinh, Lê Thị Thanh (VNU Journal of Science: Natural Sciences and Technology, 1999)
Tóm tắt